Approach to work process concerning family health project at a health center from Campinas city, Brazil - Mellin, Aparecida Silvia; Pinto, Adriana Gomes (Revista de Enfermagem UFPE on line, 2008)
ABSTRACT Qualitative study with the main objective of learning the work process of health professionals, analyzing their way of conceiving municipal health politics, and the daily actions of the “Paidéia” Family Health Municipal Project. Achieved using interviews applied to a coordinator of a Health Center in the city from Campinas and several of the health family team professionals. Results could be observed that, despite not having thought uniformity concerning the assistance model, all of them noticed the qualities of the project, concerning the lines of directions of “Paideia”. Nevertheless, they elaborated critics related to the daily experience on service, especially on human resources insufficiency. It was concluded that the project adoption in 2001, did not allowed the complete adhesion of the professionals and the structure resources adequacy and work process, which could be characteristic of the transition and the recently proposed practices coexistence with those previously applied. Descriptors: family health; health professionals; work process; unique health system. RESUMO Estudo qualitativo com objetivo de apreender o processo de trabalho de profissionais de saúde analisando suas formas de conceber políticas de saúde municipais, bem como as ações cotidianas no Projeto “Paidéia” de Saúde da Família. Realizado com uso de entrevistas com o coordenador de um Centro de Saúde de Campinas e vários profissionais da equipe de saúde da família. Pode-se observar que, apesar de não haver uniformidade de pensamento sobre o modelo assistencial, todos consideram as qualidades do projeto, no que diz respeito ao cumprimento das diretrizes do “Paidéia”. Apesar disto, elaboram críticas relacionadas às vivências cotidianas no serviço, em especial à insuficiência de recursos humanos. Concluiu-se que adoção do projeto, em 2001, não permitiu a completa adesão dos profissionais e a adequação dos recursos de estrutura e processo de trabalho, o que pode ser característico de momentos de transição e da coexistência de práticas recém propostas com anteriores. Descritores: saúde da família; profissionais de saúde; processo de trabalho; sistema único de saúde. RESUMEN Estudio cualitativo con el objetivo de aprender el proceso de trabajo de profesionales de la salud analizando sus formas de concebir políticas municipales de la salud, bien como las acciones cotidianas en el Proyecto “Paidéia” de Salud de la Familia, realizado en 2003 haciendo uso de entrevistas con el coordinador de un Centro de Salud de Campinas, y varios profesionales del equipo de la salud de la familia. Se puede observar que, a pesar de no haber uniformidad de pensamiento sobre el modelo asistencial, todos consideran la calidad del proyecto en lo que dice respecto a las directrizes del Paidéia. A pesar de esto, elaboran críticas relacionadas al diario vivir en el trabajo, en especial a la insuficiencia de recursos humanos. Se concluye que la adopción del proyecto en 2001, no permitió una adhesión completa de los profesionales, la adecuación de los recursos de la estructura y el proceso de trabajo, lo que puede ser característico de momentos de transición y de la coexistencia de prácticas recién propuestas, con las anteriores. Descriptores: salud de la familia; profesionales de la salud; proceso de trabajo; sistema único de salud.